In the Thick of It: Formation of the Tuberculous Granuloma and Its Effects on Host and Therapeutic Responses - Cronan, Mark R. (Frontiers in Immunology, 2022)
The defining pathology of tuberculosis is the granuloma, an organized structure derived from host immune cells that surrounds infecting Mycobacterium tuberculosis. As the location of much of the bacteria in the infected host, the granuloma is a central point of interaction between the host and the infecting bacterium. This review describes the signals and cellular reprogramming that drive granuloma formation. Further, as a central point of host-bacterial interactions, the granuloma shapes disease outcome by altering host immune responses and bacterial susceptibility to antibiotic treatment are discussed. This new understanding of granuloma biology and the signaling behind it highlights the potential for host-directed therapies targeting the granuloma to enhance antibiotic access and tuberculosis-specific immune responses.